STRONG CONVERGENCE THEOREMS FOR A COMMON FIXED POINT OF NONEXPANSIVE MAPPINGS IN BANACH SPACES - Tuyen, T. M. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this paper, we introduce some strong convergence theorems for the problem of finding a common fixed point of a finite family of nonexpansive mappings in Banach spaces by the combination the regularization method and the viscosity approximation method.